Regional Variation in Insularity Effects on Acorn Herbivory in European Oaks Challenges Predictions of Lower Herbivory on Islands - Irene Virseda; Luis Abdala‐Roberts; Miquel Capó; Ayco J. M. Tack; Johan A. Stenberg; Finn Hansen; Felisa Covelo; Beatriz Lago‐Núñez; Nikolaos M. Fyllas; Raúl de la Mata; Joana Cursach; Xoaquín Moreira; et al. (Journal of Biogeography, 2025)
Aim Ecological theory predicts lower herbivory on islands. However, most island‐mainland comparisons have focused on vegetative tissues, while reproductive structures remain understudied despite their direct influence on plant fitness and recruitment. This study investigates how insularity affects insect herbivory in oak ( Quercus ) acorns across multiple island‐mainland regions and explores the role of acorn traits (chemical defences and nutrients) and climate as potential drivers. Location Three island‐mainland regions in Europe: Lesbos Island—mainland Greece, the Balearic Islands—mainland Spain, and Bornholm Island—mainland Sweden. Time Period Acorns were collected in autumn 2023. Climatic data are long‐term averages for each population. Major Taxa Studied Seven oak ( Quercus ) species across regions. Methods We aimed to sample up to three island and three mainland populations per species, with four trees per population, but logistical constraints reduced these numbers, resulting in a total of 150 sampled trees. We assessed acorn damage by insect herbivores and analysed chemical defences (phenolics) and nutrients (nitrogen and phosphorus) to test their influence on island–mainland differences in herbivory. Climatic data from the WorldClim database were used to assess climate‐mediated insularity effects on acorn traits and herbivory. Results Acorn damage did not differ overall between mainland and island populations. However, in the Balearic Islands, damage was higher than in mainland Spain, while no significant differences were found in the other regions. There were no general insularity effects on acorn traits, but a region‐by‐insularity interaction influenced phosphorus levels, with higher values in mainland Sweden than Bornholm Island, while the reverse was observed in Greece. Climate influenced acorn traits, but trait differences did not explain herbivory patterns. Main Conclusions Our findings challenge the expectation that insularity reduces herbivory, highlighting region‐specific processes. While climate influenced acorn traits, these traits did not mediate insularity effects on herbivory, suggesting local ecological factors drive variation across regions.